Leveraging Social Science for Youth Sport Engagement: Enhancing Awareness and Consumption of the Youth Olympic Games - Judge, Lawrence W.; Moore, Matt; Petersen, Jeffrey; Bellar, David; Judge, Amy; Reynolds, Jerry (ASEAN Journal of Sport for Development and Peace, 2025)
The Youth Olympic Games (YOG) provides a unique platform for young athletes to compete and develop, yet there is a pressing need to understand its broader impacts on youth sports culture and development globally. Objective: This study addresses the need for a deeper understanding of public awareness and consumption intentions of the YOG considering its potential for promoting social cohesion within the Sport for Development (SFD) framework. Instruments and Methods: Utilizing a cross-sectional survey conducted during the Buenos Aires YOG, 140 usable surveys were analyzed to examine awareness and consumption intentions. Results: Results reveal significant sex and athlete-type disparities in awareness and event participation, with males and recreational athletes displaying higher levels of awareness and engagement compared to females and competitive athletes. Findings and Discussion: These findings underscore the necessity for targeted interventions to increase inclusivity and engagement among underrepresented groups. A collaborative approach, involving sports social workers and local partners, is recommended to enhance awareness and participation. By promoting the YOG as a catalyst for social cohesion and community development, its impact can be amplified. Additionally, activating the support of ex-athletes could further elevate the YOG profile. These insights provide a strategic guide for expanding the reach of the YOG and advancing SFD outcomes.